The possibilities of ultrasound imaging in the diagnosis of follicular neoplasia of the thyroid gland - D. D. Dolidze; Z. A. Bagatelia; A. Yu. Lukin; S. D. Сovantsev; T. V. Shevyakova; N. V. Pichugina; D. M. Skripnichenko; K. A. Mulaeva (Опухоли головы и шеи, 2023)
Thyroid cancer is the most common cancer of the endocrine system. The diagnosis of thyroid cancer has taken a step forward due to the introduction of fine-needle biopsy of the thyroid gland with subsequent evaluation of cytological material using the Bethesda system. One category of this classification traditionally remains a gray area of diagnosis. The detection of a follicular tumor in the cytological material (category IV according to Bethesda) does not allow one to reliably classify the neoplasia as benign or malignant and requires surgical intervention. The traditional informative and widely used method for diagnosing thyroid tumors is ultrasound. However, the sensitivity and specificity of the method varies over a wide range. This review analyzes the literature on the possibilities of ultrasound diagnostics in assessing the malignant potential of follicular tumors of the thyroid gland.